Czech republic 2000 : ten years on: environment and quality of life after ten years of transition - Moldan, Bedřich; Hák, Tomáš (Charles University, 2000)
The report focuses on the changes in environment and quality of life in Czechia from 1989 to 1999. Written for professional public.
Keywords: dějiny 20. století; Czech Republic; veřejné zdravotnictví; životní prostředí; znečištění životního prostředí; Vital Statistics; statistika přirozeného pohybu; Environmental Pollution; Socioeconomic Factors; demografie; socioekonomické faktory; Environment; Quality of Life; History, 20th Century; Česká republika; environmentální vědy; kvalita života